Andean pre-Hispanic pottery forming 3D analysis: a pilot study from Quebrada de Humahuaca (Argentina) using digital methods - Scaro, Agustina (2022)
Digitization, three-dimensional (3D) documentation and visualization of archaeological materials are processes in increasing development that are used for enhancing heritage. These tools have multiple uses for the analysis and research of archaeological objects, although their use in pottery forming techniques studies is less explored. In this paper, diverse digital methods are analysed in the study of pottery forming macro-traces, using the 3D model of an archaeological vessel from South-Central Andes. This case is proposed as a pilot study, aiming to reveal the digital techniques’ potential for understanding pottery forming techniques. The particular case dealt with corresponds to a globular pot of the Humahuaca Black-on-Red style, recovered at the Pucara de Volcán archaeological site, in Quebrada de Humahuaca (Jujuy, Argentina). Initial studies of macro-traces on the pot suggested the use of paddling as the forming technique. To contrast this hypothesis, the workflow applied included the generation of a 3D model by close-range photogrammetry; the author also analysed the resulting point cloud and mesh using Morphological Residue Model (MRM) and Virtual Reflectance Transformation Imaging visualization (V-RTI). This was possible thanks to various open-source software packages, such as AliceVision Meshroom and CloudCompare. These methods increased the micro-topography visibility of the pot surface. As a result, the presence of sub-circular depressions in the body of the pot-similar to percussion cupules-, horizontal pressure lines in the collar, and micro-pull-outs in the maximal diameter of the pot were described. These macro-traces were interpreted as corresponding to the paddling technique used for the elaboration of the pot body —a technique not previously identified in pre-Hispanic traditional pottery manufacturing in the north of Argentina—, and of coiling for manufacturing the collar. The digital methods explored have great potential in the study of pottery forming techniques, although their scope depends on the accuracy of the 3D model analysed.